Anisotropic He-ion irradiation damages in nanocolumnar W thin films. (November 2020) - Oh, Injun; Park, Donghyun; Cheong, Euimin; Jo, Haechan; Park, Sanghun; You, Daegun; Kim, Taeyeop; Park, Yuhyun; Kim, Kyunghoon; Sim, Gi-Dong; Shin, Chansun; Lee, Dongwoo
Abstract: The effects of He-ion irradiation on the microstructures and the mechanical, thermal properties of sputter-deposited nanocolumnar tungsten thin films have been studied. 200 keV He + ion irradiation with a fluence of 2x10 17 ions/cm 2 was performed in the growth direction of the W thin films. Small scale mechanical testing methods, such as nanoindentation and square membrane deflection experiments, were carried out, and the thermal conductivity measurement was performed based on the electrical resistivity measurement and the Wiedemann–Franz law for the unirradiated and irradiated W thin films. It was revealed that the properties in the out-of-plane direction are not changed much, but a significant degradation occurs in the in-plane direction after the He-ion irradiation. The microstructure of the film and the distribution of He-ion induced damages are responsible for the anisotropic property changes by He-ion irradiation.